Polymer and composite materials used in medicine - an overview - Oleksy, Małgorzata; Dynarowicz, Klaudia; Aebisher, David (Polimery, 2023)
The article is a review of the literature on the use of polymers in medicine as biomaterials. Examples of the preparation of the most commonly used synthetic polymers in medicine, such as: polylactide (PLA), polyglycolide (PGA), polyhydrobutyrate (PHB), polycaprolactone (PCL) are described. The characteristics of ceramic materials: hydroxyapatite (HAp) and tricalcium phosphate (TCP) are also presented in terms of the use of synthetic biodegradable polymers as biofillers. The last part of article is devoted to the functional properties of composites based on PLA with the addition of HAp and TCP.